Effects of dietary extra virgin olive oil and its fractions on antioxidant status and DNA damage in the heart of rats co-exposed to aluminum and acrylamide1. Issue 9 (2nd September 2015) - Ghorbel, Imen; Khemakhem, Mouna; Boudawara, Ons; Marrekchi, Rim; Jamoussi, Kamel; Ben Amar, Raja; Boudawara, Tahia; Zeghal, Najiba; Grati Kamoun, Naziha
<x xml:space="preserve">Abstract</x> Oxidative stress generated by an excessive production of free radicals has been linked to the development of several health problems such as cardiovascular diseases.